Using Genetic Algorithm to Estimate the Parameters of the Gumbel Distribution Function by Simulation - Jasim Mohammed, Salam; Khalid Khudair, Ali; kadhum shaffeq , Shurooq (Journal of Economics and Administrative Sciences, 2022)
In this research, the focus was on estimating the parameters on (min- Gumbel distribution), using the maximum likelihood method and the Bayes method. The genetic algorithmmethod was employed in estimating the parameters of the maximum likelihood method as well as  the Bayes method. The comparison was made using the mean error squares (MSE), where the best  estimator  is the one who has the least mean squared error. It was noted that the best estimator was (BLG_GE).